2017
DOI: 10.3233/jad-160858
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Synaptic Plasticity and Glutamate Receptors in Type 2 Diabetic KK-Ay Mice

Abstract: In the present study, the progressive alteration of cognition and the mechanisms of reduction in long-term potentiation (LTP) in spontaneous obese KK-Ay type 2 diabetic mice were investigated. In the study, 3-, 5-, and 7-month-old KK-Ay mice were used. The results indicated that KK-Ay mice showed cognitive deficits in the Morris water maze test beginning at the age of 3 months. LTP was significantly impaired in KK-Ay mice during whole study period (3 to 7 months). The above deficits were reversible at an early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
2
15
0
2
Order By: Relevance
“…Our study demonstrated that KK‐Ay mouse is a stable and useful model of T2DM and the mice showed obviously cognitive deficiency in Morris water maze test. It was similar to the previous studies, which KK‐Ay mice displayed a cognitive dysfunction at quite young with low activity of long‐term potentiation (LTP) . However, diabetes‐induced dementia is different from AD in pathogenesis.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our study demonstrated that KK‐Ay mouse is a stable and useful model of T2DM and the mice showed obviously cognitive deficiency in Morris water maze test. It was similar to the previous studies, which KK‐Ay mice displayed a cognitive dysfunction at quite young with low activity of long‐term potentiation (LTP) . However, diabetes‐induced dementia is different from AD in pathogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…Our previous study had shown that the body weight, random blood glucose, cholesterol, triglyceride, and insulin of KK‐Ay mice were significantly increased compared to control age‐matched group at 3,5, and 7 months of age, which suggested that KK‐Ay is a reliable model of T2DM . Furthermore, KK‐Ay mice showed obvious spatial learning and memory deficits in the diabetic duration .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations